Revitalisasi SMK Menuju Tuntutan Keterampilan Abad 21 - Ade Firdaus (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
his study aims to determine: 1. Strategy for Fulfilling Facilities and Infrastructure at SMKN 2 Pandeglang. 2. Strategy The high interest of junior high school graduates to continue to SMKN 2 Pandeglang. 3. High Discipline of Students and Students of SMKN 2 Pandeglang. 4. High Absorption of Graduates to DU / DI. 5. High quality of human resources. 6. Fulfillment of 21st Century skill demands. The results show (1) the FOCUS strategy is very appropriate in learning facilities and infrastructure. SMKN 2 Pandeglang fulfilled to get to SMK Revitalization. (2) The FOCUS strategy is very appropriate in the interest of junior high school graduate students to continue to SMKN 2 Pandeglang Tinggi. It can be seen from the results that there are 5 educators taken in the sample and 10 students answered on a scale of 5, that means the interest of junior high school graduates to continue to SMKN 2 Pandeglang Tinggi to SMKN 2 Pandeglang fulfilled to get to SMK Revitalization. (3) The FOCUS strategy is very appropriate in High Discipline. It can be seen from the results that there are 5 educators taken as a sample and 10 students answer on a scale of 5, it means that High Discipline is fulfilled to get to SMK Revitalization. (4) The FOCUS strategy is very precise in terms of the absorption capacity of High graduates. It can be seen from the results that 9 students answered on a scale of 5, it means that the absorption capacity of High graduates is fulfilled to get to SMK Revitalization. (5) The FOCUS strategy is very appropriate in the Quality of High Human Resources. It can be seen from the results that there are 5 educators taken as a sample and 10 students answer on a scale of 5, it means that the High Quality of Human Resources is fulfilled to get to SMK Revitalization. (6) The strategy taken by the author is the right strategy to answer the demands of 21st Century skills, because with a focus on SMKN 2 Pandeglang it can reach the National Revitalization School.